Language and colonial power : the appropriation of Swahili in the former Belgian Congo, 1880-1938 - Fabian, Johannes (University of California Press, 1991)
In this study, inquiry will be directed to the past, and it will, for many reasons, have to reach into a past which is rather remote from present-day Shaba Swahili. The author's principal concern remains with a contemporary situation, namely the role of Swahili in the context of work, industrial, artisanal, and artistic. When it was first formulated, the aim of my project was to describe what might be called the workers' culture of Shaba, through analyses of communicative (sociolinguistic) and cognitive (ethnosemantic) aspects of language use.